2022
DOI: 10.2196/38690
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With a Mobile Digital Health Platform for Patients Undergoing Spine Surgery: Retrospective Analysis

Abstract: Background Digital health solutions have been shown to enhance outcomes for individuals with chronic medical illnesses, but few have been validated for surgical patients. The digital health platform ManageMySurgery (MMS) has been validated for spine surgery as a feasible method for patients along their surgical journey through in-app education and completion of patient-reported outcomes surveys. Objective The aim of this study is to determine the rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…A large proportion of the approached patients wanted to participate in the study, and once they started with the intervention, almost all participants used it until the posttest assessment and final interview. The willingness to use a digital health intervention seemed quite high in our study compared with in previous studies [ 67 , 68 ]. It seems that, once participants started the intervention in this study, they saw its value and kept using it over a longer period.…”
Section: Discussioncontrasting
confidence: 57%
“…A large proportion of the approached patients wanted to participate in the study, and once they started with the intervention, almost all participants used it until the posttest assessment and final interview. The willingness to use a digital health intervention seemed quite high in our study compared with in previous studies [ 67 , 68 ]. It seems that, once participants started the intervention in this study, they saw its value and kept using it over a longer period.…”
Section: Discussioncontrasting
confidence: 57%
“…The oncologic literature suggests patients who routinely report symptoms through digital health platforms have a lower symptom burden due to the increased awareness of serious adverse reactions and earlier detection by patients and providers [48]. Furthermore, by providing education to patients, expectations are more easily managed, and there is a reduction in patient visits to emergency departments [49].…”
Section: Discussionmentioning
confidence: 99%
“…Through this application, the research team was able to collect patient-reported outcome measures, offer self-monitoring features, answer frequently asked questions, and provide educational materials on the patient's surgery [91]. In a larger follow-up study of over 1000 patients, Venkatraman et al found that spine surgery patients making use of this app experienced fewer 90-day readmissions and were 32% less likely to visit the emergency room within 90 days following their surgery [6]. Although these tools are cost-effective means to provide patients with information and collect data, it is important that patients are not overly reliant on such technology and delay presentation for a concerning postoperative development.…”
Section: Digital Care Pathwaysmentioning
confidence: 99%
“…Improvements in perioperative care have mirrored advances within the operating room, and helped optimize patient selection, management of comorbid conditions, and return to baseline functional status following surgery. Measures ranging from enhanced recovery after surgery (ERAS) protocols to digital health solutions, like smart phone applications and wearable medical devices, reflect an increasing emphasis on the postoperative management of patients undergoing minimally invasive spine surgery [5,6].…”
Section: Introductionmentioning
confidence: 99%